Asap1 Affects the Susceptibility of Zebrafish to Mycobacterium by Regulating Macrophage Migration - Cui, Jia; Chen, Guangxin; Wen, Da; Wang, Yuhuan; Zhao, Zhonghua; Wu, Changxin (Frontiers in Cellular and Infection Microbiology, 2020)
The ADP ribosylation factor (ARF) GTPase activation protein ASAP1 possesses multiple biological functions, including regulation of cytoskeletal dynamics, small GTP-binding protein receptor recycling, and intracellular vesicle trafficking. Recently, ASAP1 polymorphisms have been reported to be associated with human susceptibility to tuberculosis (TB) according to a large-scale genome-wide association study (GWAS); ASAP1 expression affects dendritic cell migration, which may be involved in TB predisposition. However, it remains unclear whether ASAP1 affects TB in vivo. To address this issue, we used zebrafish as a model system to examine the effects of Asap1 against Mycobacterium marinum, an organism closely related to Mycobacterium tuberculosis. Two zebrafish asap1 homologs (asap1a and asap1b) were identified and characterized. By morpholino knockdown of asap1a and asap1b as a whole, we found that the asap1 morphants showed a higher mycobacterial load than the controls, which was almost rescued by injecting asap1 mRNA that confers resistance to mycobacterial infection. These Asap1-depleted zebrafish also exhibited decreased macrophage migration in response to tail injury or upon infection with M. marinum in the hindbrain ventricle, which was also proved in THP1-derived macrophages of knockdown ASAP1. Together, these findings represent a new perspective on the role of Asap1 in resistance to mycobacterial infection.